2018
DOI: 10.3390/cells7040031
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Shifted Red Blood Cells: A Novel Red Blood Cell Stage?

Abstract: Primitive nucleated erythroid cells in the bloodstream have long been suggested to be more similar to nucleated red cells of fish, amphibians, and birds than the red cells of fetal and adult mammals. Rainbow trout Ficoll-purified red blood cells (RBCs) cultured in vitro undergo morphological changes, especially when exposed to stress, and enter a new cell stage that we have coined shape-shifted RBCs (shRBCs). We have characterized these shRBCs using transmission electron microscopy (TEM) micrographs, Wright–Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 53 publications
2
33
1
Order By: Relevance
“…Besides, we have not found any report showing nucleated RBCs expressing the protein encoded by a DNA vaccine in vivo . GVHSV-transfected RBCs showed a characteristic perinuclear expression of GVHSV protein that appeared in the perinuclear region of stressed RBCs or on the membrane of shape-shifted RBCs (shRBC) ( 33 ). shRBCs are small, round cells with a thin membrane derived from RBCs subjected to stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we have not found any report showing nucleated RBCs expressing the protein encoded by a DNA vaccine in vivo . GVHSV-transfected RBCs showed a characteristic perinuclear expression of GVHSV protein that appeared in the perinuclear region of stressed RBCs or on the membrane of shape-shifted RBCs (shRBC) ( 33 ). shRBCs are small, round cells with a thin membrane derived from RBCs subjected to stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…shRBCs are small, round cells with a thin membrane derived from RBCs subjected to stressful conditions. Translation of the GVHSV gene into protein and translocation to the cell membrane induces RBC transformation into stressed RBC and shRBC ( 33 ). Like RBCs, shRBCs have been shown to participate in roles related to immune response and homeostasis ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the rainbow trout (O. mykiss), immune responses also involve shRBCs (shape-shifted RBCs) whose morphology has been changed owing to thermal stress in the in vivo environment (5). They are characterized by, e.g., a round shape, hemoglobin loss, and expression of new, IgM-like markers (5). These cells show the ability to inhibit VHSV infection as well as antiviral activity, which is manifested by increased expression of IL8, IL1, IFNγ, and NKEF.…”
Section: Viral Hemorrhagic Septicemia Virusmentioning
confidence: 99%
“…In Osteichthyes, RBCs can also contribute to elimination of pathogens/antigens, bound in the immune complexes containing the complement, through their recognizing and binding by the complement receptor 1 (CR1) (12). These cells show phagocytic properties (erythrophagocytosis) (12,13), are capable of reacting with various pathogen-associated molecular patterns via pattern recognition receptors, e.g., peptidoglycan recognition proteins, as well as Toll-like receptors (TLRs) and retinoic acid-inducible gene-I-like receptors (RIG-I-like receptors) (2,5,14). Moreover, erythrocytes of Osteichthyes are probably involved in the immune response as the antigen-presenting cells (APCs), via major histocompatibility complex (MHC) class II antigens, and they can contribute to formation of immune synapse with T cells and NK (natural killer) cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that chicken RBCs stimulated with fungal species Candida albicans release cytokine-like factors with IFNγ-like activity [33]. The conditioned medium of shape-shifted RBCs (shRBCs), a new cell stage of rainbow trout RBCs, induced communication with rainbow trout stromal pronephros cells (TPS-2 cells) and resulted in the upregulation of IFNγ-activated genes in this cell line [34].…”
Section: Nucleated Rbcs Induce Interleukin Responsementioning
confidence: 99%